METHODOLOGY OF THE DRUGS MARKET VOLUME MODELING ON THE EXAMPLE OF HEMOPHILIA A - N. B. Molchanova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Hemophilia A is a serious genetic disease, which may lead to disability of a patient even in early ages without a required therapy. The only one therapeutic approach is a replacement therapy with drugs of bloodcoagulation factor VIII (FVIII). The modeling of coagulation drugs market volume will allow evaluation of the level of patients' provision with a necessary therapy. Modeling of a "perfect" market of drugs and its comparison with the real one was the purpose of the study. During the modeling of market volume we have used the data about the number of hamophilia A patients on the basis of the federal registry, Russian and international morbidity indices, and the data of a real practice about average consumption of drugs of bloodcoagulation factors and data about the drugs prescription according to the standards and protocols of assistance rendering. According to the standards of care delivery, average annual volume of FVIII drugs consumption amounted to 406 325 244 IU for children and 964 578 678 IU for adults, i.e. an average volume of a "perfect" market is equal to 1 370 903 922 IU for all patients. The market volume is 1.8 times bigger than a real volume of FVIII drugs which, according to the data of IMS marketing agency, amounted to 765 000 000 IU in 2013. The modeling conducted has shown that despite a relatively high patients' coverage there is a potential for almost double growth.